Implementasi Nilai Tri Kaya Parisudha Dalam Moderasi Beragama: (Persepektif Bhagawad Gita Dan Sarasamuscaya) - Suterji, Ni Ketut; Lestari, Ni Putu Prawani Uma; Sepriani, Ni Kadek (Jayapangus Press, 2024)
Religious Moderation is a government program to achieve harmony in the lives of Indonesian people with diverse beliefs, cultures and languages. Every religion recognized in Indonesia has authentic sources that can support religious moderation, and Hinduism is no different. This research aims to examine more deeply the implementation of Tri Kaya Parisudha, including cleanliness of mind (manacika parisudha), cleanliness of words (wacika parisudha) and cleanliness of actions (kayika parisudha) to achieve religious moderation. This research is classified as descriptive qualitative research with a library research method, namely studying the sacred library texts of the Bhagavad Gita and Sarasamuscaya, and in-depth interviews with Hindu religious figures who were determined deliberately (purposive sampling). Data were analyzed using qualitative descriptive methods. Based on the analysis of the results and discussion, it is concluded that the teachings of Religious Moderation are found in the teachings of the Bhagawad Gita and Sarasamuscaya which are implemented in the Tri Kaya Parusdha teachings. The implementation of the Tri Kaya Parisudha values ​​in Religious Moderation in Indonesia is made easier by increasing understanding and grounding the teachings of the Bhagavad Gita and Sarasamuscaya, which aims to build good character and attitudes of Hindus. Having a good Hindu character facilitates social relations between, internal and external religious communities in Indonesia so that tolerance, order and peace in society are conducive.